2007
DOI: 10.1016/j.neuroscience.2006.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Dynorphin-containing axons directly innervate noradrenergic neurons in the rat nucleus locus coeruleus

Abstract: Stress causes increased dynorphin (DYN) expression in limbic brain regions and antagonism of kappa-opioid receptors may offer therapeutic potential for the treatment of depression. A potential site of DYN action relevant to stress and related neuropsychiatric disorders is the locus coeruleus (LC), the primary source of forebrain norepinephrine. Therefore, using immunofluorescence and immunoelectron microscopic analyses, we characterized the cellular substrates for interactions between DYN and tyrosine hydroxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 77 publications
2
57
0
Order By: Relevance
“…The locus coeruleus (LC) is one of the primary sources of norepinephrine (NE) in the forebrain [81] . Dynorphin and κ opioid receptors are coexpressed within the LC on noradrenergic (NA) neurons [67,[82][83][84][85] . Previous reports have shown that both stress and CRF engage in LC NA cell firing [86,87] .…”
Section: Brain Regions Involved In κ Opioid Receptor-mediated Anxietymentioning
confidence: 99%
“…The locus coeruleus (LC) is one of the primary sources of norepinephrine (NE) in the forebrain [81] . Dynorphin and κ opioid receptors are coexpressed within the LC on noradrenergic (NA) neurons [67,[82][83][84][85] . Previous reports have shown that both stress and CRF engage in LC NA cell firing [86,87] .…”
Section: Brain Regions Involved In κ Opioid Receptor-mediated Anxietymentioning
confidence: 99%
“…The specificity of ppDYN antiserum was tested by absorption controls with the cognate peptides (Arvidsson et al, 1995;Reyes et al, 2007). Preabsorption of ppDYN with the antigenic peptide at 1 μM blocked the immunoreactivity in regions known to express DYN (hippocampus, spinal cord).…”
Section: Specificity Of Antiseramentioning
confidence: 99%
“…Additionally, kappa opioid receptor (κ-OR) antagonists prevent stress-elicited behaviors that are endpoints of depression such as immobility in the forced swim test and passive behavior in learned helplessness (Mague et al, 2003;McLaughlin et al, 2003;Shirayama et al, 2004). Our recent evidence for DYN-immunoreactive terminals targeting tyrosine hydroxylase (TH)-immunoreactive perikarya and processes in the LC (Reyes et al, 2007) showed that the majority of synaptic specializations observed were asymmetric synapses suggesting coexisting excitatory transmitters such as glutamate or CRF. These data have compelled us to consider the impact of this additional opioid peptide family in our model of co-regulation of the LC system by endogenous opioids and the stress peptide, CRF.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, LC innervation by the -OR ligand, dynorphin, was identified (Reyes et al, 2007) and others have demonstrated -OR mRNA and protein in the LC (DePaoli et al, 1994;Mansour et al, 1994), suggesting that this system regulates LC activity. This is of particular interest as dynorphin and -ORs are implicated in stress-related disorders (Pliakas et al, 2001;Mague et al, 2003;McLaughlin et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%